2014
DOI: 10.1016/j.abb.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The role of melanogenesis in regulation of melanoma behavior: Melanogenesis leads to stimulation of HIF-1α expression and HIF-dependent attendant pathways

Abstract: To study the effect of melanogenesis on HIF-1α expression and attendant pathways, we used stable human and hamster melanoma cell lines in which the amelanotic vs melanotic phenotypes are dependent upon the concentration of melanogenesis precursors in the culture media. The induction of melanin pigmentation led to significant up-regulation of HIF-1α, but not HIF-2α, protein in melanized cells for both lines. Similar upregulation of nuclear HIF-1α was observed in excisions of advanced melanotic vs. amelanotic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
206
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(213 citation statements)
references
References 106 publications
7
206
0
Order By: Relevance
“…HIF-1α was observed to be upregulated in advanced MM compared with melanocytic nevi or thin melanomas localized to the skin (17). However, the regulatory mechanism of HIF-1α expression in MM has yet to be elucidated.…”
Section: Microrna-138 Suppresses Proliferation Invasion and Glycolysmentioning
confidence: 96%
“…HIF-1α was observed to be upregulated in advanced MM compared with melanocytic nevi or thin melanomas localized to the skin (17). However, the regulatory mechanism of HIF-1α expression in MM has yet to be elucidated.…”
Section: Microrna-138 Suppresses Proliferation Invasion and Glycolysmentioning
confidence: 96%
“…Many published studies confirmed that melanin can increase the resistant of melanotic melanomas to chemo-, radio-and phototherapy. Therefore, anti-tyrosinase and antioxidant compounds have been able to prevent cellular mutations and tumor cells growth and increase therapeutic effectiveness of anti-melanoma drug through melanogenesis inhibition (3,4).…”
Section: Mpc Groupmentioning
confidence: 99%
“…ROS can cause extensive cellular damage and decrease enzymatic antioxidant defense. Based on these observations, melanogenesis is involved in several human skin disorders, including pigmentation disorders and melanoma (3)(4)(5). Therefore, suppressing melanogenesis through inhibition tyrosinase activity together with increasing antioxidant status can be an effective strategy to achieve both anti-melanogenic and antimelanoma properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanin has been established as a protective factor against ultraviolet radiations. Disparity in the synthesis of melanin has also been associated with pre-cancerous, benign and patchy skin lesions, such as, vitiligo, lentigo, ephelis, naevi, macules and melanoma (7,8,9). Melanin related intracellular stress is associated with an increased expression of certain mitochondrial heat shock proteins such as mortalin, HSP60 and HSP70 (6).…”
Section: Introductionmentioning
confidence: 99%